Mathematics of Biology Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Cortona (Arezzo), Italy, June 18-30, 1979 - Iannelli, Mimmo (C.I.M.E. Summer Schools, 2011)
K.L. Cooke: Delay differential equations.- J.M. Cushing: Volterra integrodifferential equations in population dynamics.- K.P. Hadeler: Diffusion equations in biology.- S. Hastings: Some mathematical problems arising in neurobiology.- F.C. Hoppensteadt: Perturbation methods in biology.- S.O. Londen: Integral equations of Volterra type.